2016
DOI: 10.1097/rli.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Macrocyclic Gadobutrol in Children Aged Younger Than 2 Years Including Term Newborns in Comparison to Older Populations

Abstract: The PK profile of gadobutrol in children aged younger than 2 years including newborns is similar to that in older children and adults. At the dose of 0.1 mmol/kg BW, gadobutrol had a favorable safety profile and was well tolerated with similar profile across the age range 0 to younger than 2 years and compared with older children and adults. Extrapolation of efficacy data from adults to the younger pediatric population, including term newborns, is justified. The recommended standard dose of gadobutrol (0.1 mmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 27 publications
6
32
0
1
Order By: Relevance
“…Clinical and observational studies on a range of indications in adults and children have demonstrated gadobutrol to be efficacious with a favourable safety and tolerability profile [1315]. At the request of the European Medicines Agency (EMA), a prospective, multicentre, non-interventional study, GARDIAN (Gadovist® in Routine Diagnostic MRI – Administration in Non-selected Patients), was initiated to evaluate the acute safety and tolerability of gadobutrol use in approved indications in a large patient population in routine practice, including the age group 2 to 7 years as well as patients with renal impairment or cardiac disease and patients considered at risk for contrast media (CM) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and observational studies on a range of indications in adults and children have demonstrated gadobutrol to be efficacious with a favourable safety and tolerability profile [1315]. At the request of the European Medicines Agency (EMA), a prospective, multicentre, non-interventional study, GARDIAN (Gadovist® in Routine Diagnostic MRI – Administration in Non-selected Patients), was initiated to evaluate the acute safety and tolerability of gadobutrol use in approved indications in a large patient population in routine practice, including the age group 2 to 7 years as well as patients with renal impairment or cardiac disease and patients considered at risk for contrast media (CM) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been used for over 25 years with an excellent safety profile other than the association with nephrogenic systemic fibrosis in those with renal impairment (2,3). Several investigations (4)(5)(6)(7) into the use of these compounds in children have shown that they are safe for use in MR examinations, and have fewer adverse outcomes in children than in adults.…”
mentioning
confidence: 99%
“…In adults and children, the majority of studies show no increased signal intensity with multiple doses of macrocyclic GBCAs. Gadobutrol (Gd-DO3A-butrol, Gadovist, Gadavist; Bayer Pharma, Leverkusen, Germany) is a secondgeneration macrocyclic GBCA used to enhance tissue contrast at MRI for a range of approved indications in adults and children of all ages (29). In December 2014, the U.S. Food and Drug Administration approved gadobutrol for use at MRI of the central nervous system in children younger than 2 years, and it is approved in many other countries for whole-body MRI in this age group (7). The American College of Radiology, European Medicines Agency, and the European Society of Urogenital Radiology placed gadobutrol in the lowest risk category for development of nephrogenic systemic fibrosis (11)(12)(13).…”
mentioning
confidence: 99%
“…The PK profile was similar to that in older children and adults. In all, 1 of 44 patients (2.3%) experienced a drug-related AE (mild vomiting), 25 whereas in a study of 57 patients <2 years, no AE was recorded. 26 …”
Section: Safetymentioning
confidence: 85%